2017
DOI: 10.2147/cmar.s148856
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of site-specific metastases and therapeutic roles of surgery for patients with metastatic bladder cancer: a population-based study

Abstract: BackgroundWe aimed to evaluate the prognostic value of site-specific metastases in patients with metastatic bladder cancer and analyze the roles that surgeries play in the treatment of this malignancy.Materials and methodsA population-based retrospective study using Surveillance, Epidemiology and End Results dataset was performed and metastatic bladder cancer patients were classified according to the sites of metastases (bone, brain, liver, lung and distant lymph nodes). Kaplan–Meier analysis with log-rank tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 34 publications
5
38
0
Order By: Relevance
“…The 2018 NCCN guidelines also suggested platinum-based chemotherapy has been standard of care in patients with metastatic disease, with an OS of 9 to 15 months (27). A previous study suggested that different distant-metastatic site and multiple sites metastasis were independent prognostic factors for OS in metastatic BC patients (28), which was consistent with our findings. As shown in nomogram, metastasis pattern was the second large contributor to prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…The 2018 NCCN guidelines also suggested platinum-based chemotherapy has been standard of care in patients with metastatic disease, with an OS of 9 to 15 months (27). A previous study suggested that different distant-metastatic site and multiple sites metastasis were independent prognostic factors for OS in metastatic BC patients (28), which was consistent with our findings. As shown in nomogram, metastasis pattern was the second large contributor to prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, we established a novel nomogroup system based on the scores of the nomogram and further proved that the new-established nomogroup could easily divided patients into different risk stratifications. Third, enlightened by one of our previous study 49 , we for the first time revealed that in SCCB patients, distant lymph node metastasis represented better survival outcomes compared with other organ metastases. Hence, in the “metastasis” item of the nomograms, we creatively divided it into four categories (M0; distant node only; other organs; distant node & other organs), which increased the predictive accuracy.…”
Section: Discussionmentioning
confidence: 78%
“…Patients with metastatic BC generally have a poor prognosis, surviving just a few months because of the ease with which it invades the muscle layer 3. In previous studies, approximately 10-15% of BC patients were reported to present at diagnosis with metastatic disease 4,5. Bone metastases (BM) were reported to be correlated with skeletal complications and decrease survival and quality of life in urogenital neoplasms patients 6-8.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that early diagnosis of BM from BC could benefit from timely medical intervention and skeletal-related events (SREs) prevention 4,7. Currently, there are no screening guidelines for performance of routine evaluation of BM in BC patients.…”
Section: Introductionmentioning
confidence: 99%